Behavioral risk factor surveillance system state survey on exposure to adverse childhood experiences (ACEs): Who declines to respond?. (August 2018) - Crouch, Elizabeth; Radcliff, Elizabeth; Strompolis, Melissa; Hartley, Samantha N.
Abstract: Background: A wealth of research has examined the prevalence and impact of adverse childhood experiences (ACEs) via various research methodologies. Some of these studies have also examined the presence of nonresponse bias, showing minimal nonresponse bias effects. More recently, many states and the District of Columbia have used the Behavioral Risk Factor Surveillance System (BRFSS) to examine ACEs, however, limited research exists on the impact of nonresponse bias in ACE studies using the BRFSS. Methods: This study used data from the 2014–2015 South Carolina BRFSS to examine nonresponse bias to the ACE module. Results: Significant differences between responders and non-responders were found for sex, age, race/ethnicity, education, income, and rurality. Findings indicate that marginalized populations were more likely to be under-represented in ACE survey data because of nonresponse, potentially limiting targeted prevention and intervention efforts. Conclusion: Future research should examine differences in health and social outcomes between responders and non-responders to the ACE module in the BRFSS and ways to increase responses from marginalized groups. Highlights: Significant differences between responders and non-responders to ACE surveys Marginalized populations are likely to be underrepresented in ACE surveys. Future research is needed to increase responses from marginalized populations.